Spatial pattern and determinants of non-condom use among sexually active young people in Nigeria: a population-based, cross-sectional study - Olufunmilayo Esther Bello; Olorunfemi Akinbode Ogundele; Oluyemi Adewole Okunlola (Scientific Reports)
Abstract Non-condom use is known as one of the risky sexual behaviors among youth and a contributing factor to the high prevalence of HIV in Nigeria. Therefore this study aimed to assess the spatial pattern and determinants of non-condom use among sexually active young people in Nigeria. The study employed a cross-sectional analysis of population-based data involving 288 males and 780 females aged 15–24 years, giving 1068 sexually active young people drawn from the 2018 NDHS. The study adopted a multi-level and spatial analysis to identify factors associated with non-condom use in Nigeria. The prevalence of non-condom use was 57.7% in this study. The spatial analysis showed that the Northeastern and South–South regions of Nigeria had a high proportion of non-condom use among young people, while the Northwest, North-Central, and Southwestern parts had low proportions of non-condom use. On multilevel analysis, the individual and community level factors associated with non-condom use included exposure to media (AOR 0.59; 95% CI 0.39–0.91) and younger age (AOR 0.72; 95% CI 0.53–0.98). Areas with a high proportion of non-condom use should receive the most attention through the promotion of condom use and education, alongside a focus on important associated factors.